A Study on the Parametric Design Parameters That Influence Environmental Ergonomics and Sustainability - López-López, Daniel; Serrano-Jiménez, Antonio; Gavilanes-Velaz-de-Medrano, Juan; Ventura-Blanch, Ferrán; Barrios-Padura, Ángela; Díaz-López, Carmen (MDPI, 2023)
The parametric design applied to the built environment is critical to creating sustainable and resilient spaces. However, this research field involves a vast and complex amount of disconnected information. Therefore, this paper aims to analyse research trends in applying parametric design to optimise sustainability and environmental ergonomics parameters in built environments. The following specific objectives are identified to meet this objective: (i) a quantitative analysis based on a systematic literature review; (ii) a qualitative review based on a performance analysis and scientific mapping; and (iii) a comparative analysis of case studies applying parametric language for the optimisation of sustainability and environmental ergonomics parameters. The 1045 research records covering 1974 to 2021 illustrate a field in development that evolves from early digital advances to climate change adaptations, the circular economy and resilience. It highlights the importance of applying bioclimatic techniques in the built environment, identifying the most optimised measures and encouraging the creation of guidelines to serve as a protocol for future studies, contributing to the existing body of knowledge by highlighting trends, establishing research themes, outlining research networks and suggesting areas for further studies
Keywords: Ergonomía; Clima - Cambios; Parametric design; Built environment; Ustainability; Environmental ergonomics; Climate change; Resilience; Circular economy